Description Of The Level Of Knowledge Of Young Women Abot Balanced Nutrition - Mamuroh, Lilis; Widiasih, Restuning; Sutendi, Ludyta Yuniar; Sukmawati, Sukmawati; Nurhakim, Furkon (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Adolescent knowledge about nutrition is very important considering that adolescents are an age group that is at risk of various diseases and heath problems, one of which is nutrition. One of the factors that influences adolescent nutrition is the level of knowledge possessed by young women. Nutritional problems in adolescents can have short-term and long-term impacts, in the short term it is caused by nutritional problems, namely on the health problems of young women themselves such as anemia, KEK, and PEM, in the long term on reproductive health and future generations because young women will become pregnant and have children and will have an impact on the quality of the children they contain. The purpose of this study was to determine the knowledge possessed by young women which includes demographic data, understanding of nutrition, the impact of undernutrition, nutritional needs for adolescents, and knowing the types of nutritious food and how to process nutritious foods.The design in this study used quantitative descriptive. The. The sample size used in this study was 84 adolescents. The sampling technique used in this research is positive sampling. The instrument was developed by researchers who examined the meaning of nutrition, the impact of malnutrition, nutritional needs and types of nutritious foods and how to process nutritious foods. The analysis in this study is univariate analysis, which aims to describe each variable to be studied, the results of the research from respondents who were the sample in this study, namely that almost all of the respondents had good knowledge of 80%, a small proportion of respondents had sufficient knowledge of 13.8% will remain and a small proportion of respondents as much as 6.3% have less knowledge about knowledge of balanced nutrition. The results of this study found that there were still students with insufficient and moderate knowledge, so activities such as nutrition health education were needed for them.